Diversity in breeding sites and distribution of Anopheles mosquitoes in selected urban areas of southern Ghana. Issue 1 (December 2017) - Mattah, Precious; Futagbi, Godfred; Amekudzi, Leonard; Mattah, Memuna; de Souza, Dziedzorm; Kartey-Attipoe, Worlasi; Bimi, Langbong; Wilson, Michael
Abstract Background Anopheles vectors of malaria are supposedly less common in urban areas as a result of pollution, but there is increasing evidence of their adaptation to organically polluted water bodies. This study characterized the breeding habitats ofAnopheles mosquitoes in the two major urban areas in southern Ghana; Accra (AMA) and Sekondi-Takoradi (STMA) Metropolitan Areas, during dry and wet seasons. Methods Anopheles mosquito larvae were sampled using standard dipping methods to determine larval densities. The origin, nature and stability of 21 randomly selected sites were observed and recorded. Mosquito larvae were reared to adults andAnopheles species identified by both morphological and molecular means. Results Sixty-six percent ofAnopheles habitats were permanent and 34% temporal, and 74.5% man-made while 25.5% were natural. Puddles and urban farm sites accounted for over 51% of allAnopheles mosquitoes sampled. The mean larval densities among the habitat types was highest of 13.7/dip for puddles and lowest of 2.3/dip for stream/river, and the variation between densities were significant (P  = 0.002). The mean larval densities were significantly higher in the wet season than in the dry season for the two study areas combined (P  = 0.0191) and AMA (P  = 0.0228). Over 99% of the 5, 802 morphologically identifiedAnopheles species wereAn. gambiae (s.l. ) of which more than 99% of the studied 898 wereAn. coluzzii (62%) andAn. gambiae (s.s .) (34%). Urban farms, puddles, swamps and ditches/ dugouts accounted for approximately 70% of allAn. coluzzii identified. Conversely, drains, construction sites, streams/rivers and "others" contributed 80% of allAn. gambiae (s.s .) sampled. The wet season had significantly higher proportion ofAnopheles larvae compared to the dry season (Z  = 8.3683, P  < 0.0001). Also, the proportion ofAnopheles mosquitoes produced by permanent breeding sites was 61.3% and that of temporary sites was 38.7%. Conclusion Taken together, the data suggest that man-made and/ or permanent habitats were the main contributors toAnopheles larval populations in the cities and that regulation of the anthropogenic processes that lead to development of breeding places and proper environmental management can drastically reduce mosquito breeding sites in urban areas of Ghana.